2020
DOI: 10.1186/s12885-020-07133-4
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular expression of arginine deiminase activates the mitochondrial apoptosis pathway by inhibiting cytosolic ferritin and inducing chromatin autophagy

Abstract: Background: Based on its low toxicity, arginine starvation therapy has the potential to cure malignant tumors that cannot be treated surgically. The Arginine deiminase (ADI) gene has been identified to be an ideal cancersuppressor gene. ADI expressed in the cytosol displays higher oncolytic efficiency than ADI-PEG20 (Pegylated Arginine Deiminase by PEG 20,000). However, it is still unknown whether cytosolic ADI has the same mechanism of action as ADI-PEG20 or other underlying cellular mechanisms. Methods: The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…This, coupled with ROS-induced DNA damage, leads to chromatin-autophagy or chromatophagy, where autolysosome fused with nuclear membrane and “extracts” broken chromatin out of nucleus [ 16 ], eventually leading to caspase-independent cell death. This was observed in prostate cancer cells [ 16 ], breast cancer cells [ 15 ]; hepatocellular carcinoma cells [ 120 ] and pancreatic cells [ 121 ].…”
Section: Arginine Deprivation and Cell Killingmentioning
confidence: 93%
“…This, coupled with ROS-induced DNA damage, leads to chromatin-autophagy or chromatophagy, where autolysosome fused with nuclear membrane and “extracts” broken chromatin out of nucleus [ 16 ], eventually leading to caspase-independent cell death. This was observed in prostate cancer cells [ 16 ], breast cancer cells [ 15 ]; hepatocellular carcinoma cells [ 120 ] and pancreatic cells [ 121 ].…”
Section: Arginine Deprivation and Cell Killingmentioning
confidence: 93%
“…Previous research has indicated that arginine starvation can induce apoptosis in cells, triggering stress responses due to the absence of arginine. This not only leads to cell cycle arrest, but also activates pathways leading to apoptosis [ 28 , 29 , 30 ]. As such, we have further investigated the specific apoptosis pathway induced by ADC.…”
Section: Resultsmentioning
confidence: 99%
“…Both in vivo and in vitro studies in TNBC have shown that arginine shortage impairs mitochondrial function, induces endoplasmic reticulum (ER) stress response, and causes tumour cell death [ 9 , 11 ]. While the effects of arginine shortage on mitochondrial function are fairly well understood [ 10 , 12 15 ], the underlying molecular mechanisms controlling the ER stress response to acute arginine withdrawal remain to be elucidated [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%